181k views
1 vote
Which shows the following expression after the negative exponents have been eliminated

m^7 n^3/mn^-1,m=0,n=0

A.m^7 n^3 n/m

B.m^7 n^3 mn

C.m^7 n^3/m(-n)

D.m n /m^7 n

2 Answers

1 vote
its a i just took the test 
User Armen Markossyan
by
5.8k points
4 votes

Answer:

A) (m^7 n^3 n) / m

Explanation:

Given:
(m^7 n^3)/(m n^-1)

Here we have to use exponent rule.

a^-1 = 1/a

So n^-1 = 1/n

Therefore,
(m^7 n^3)/(m . (1)/(n) )

If we have fraction in the denominator, we can flip and multiply, so we get

= (m^7 n^3 n) / m

Answer is A) (m^7 n^3 n) / m

Hope this will helpful.

Thank you.

User Ravi Sachaniya
by
5.7k points